Spent brewer's yeast (Saccharomyces cerevisiae) as a potential source of bioactive peptides: An overview - Oliveira, Ana Sofia; Ferreira, Carlos; Pereira, Joana Odila; Pintado, Manuela E.; Carvalho, Ana P. (International journal of biological macromolecules, 2022)
Bioactive peptides become popular in several economic sectors over the years as they have demonstrated important biological benefits in digestive, immune, cardiovascular, and nervous human systems. Although many commercial peptides are chemically synthesized, they can also be obtained from natural protein sources such as spent brewer's yeast (Saccharomyces cerevisiae). The recovery of this fermentation by-product for production of functional ingredients is an important step in the increasingly demand to implement and promote a circular economy-based industry. Bioactive peptides can be found in protein-rich extracts produced from S. cerevisiae, and several studies have described their positive impact of human body. In this line, the present review highlights and discuss the reported biological properties of S. cerevisiae bioactive peptides in terms of antihypertensive, antioxidant and antimicrobial effects, although other bioactivities are also described. Concerning the growing interest in yeast protein-rich products by agri-food and cosmetic sectors, some of the products currently on the market are also pointed out and their potential source is discussed. [Display omitted]